Strengthening Dispute Resolution Autonomy Through Acehnese Customary Institutions: Living Law and Maqāṣid al-Sharī‘ah Perspectives - Siti Rohmah; Moh Fadli; Ngesti Dwi Prasetyo; Airin Liemanto; Zainal Arifien (TRUNOJOYO LAW REVIEW, 2026)
This study examines the urgency of strengthening the autonomy of legal dispute resolution through customary institutions in Aceh by engaging Eugen Ehrlich’s Living Law theory and Jasser Auda’s maqāṣid al-sharī‘ah framework. Aceh’s distinctive juridical and sociocultural status positions customary institutions as key actors in maintaining social cohesion and delivering justice grounded in local wisdom. However, their role is often marginalized by state legal formalism, creating a gap between statutory law and lived legal realities. This research employs a qualitative juridical-sociological approach, using literature review and document analysis. It conceptualizes customary institutions as expressions of Living Law that operate in alignment with the objectives of Islamic law, particularly the protection of life, intellect, dignity, and property. Auda’s systemic and multidimensional conception of maqāṣid al-sharī‘ah provides an analytical lens to understand these institutions as adaptive and participatory legal mechanisms. The findings demonstrate that strengthening the autonomy of customary dispute resolution reflects legal pluralism and contributes to substantive justice rather than legal conservatism. This study offers a methodological contribution by integrating Living Law and maqāṣid al-sharī‘ah in rethinking national legal development. It recommends stronger juridical recognition and institutional empowerment of customary institutions within Indonesia’s legal system.